Analysis of the Influence of Social Media and Electronic Word of Mouth on Purchase Interest at Zalora Indonesia (Jurnal Ilmu Manajemen dan Bisnis, 2024)
This study aims to describe social media, electronic word of mouth and purchase intention, analyze the influence of social media and electronic word of mouth on purchase intention, and analyze the dominant variable between social media and electronic word of mouth on purchase intention at Zalora Indonesia .This research was conducted at Zalora Indonesia with 134 sample respondents. The method used in this research is descriptive method. This study used aaccidental sampling using data collection tools through an online questionnaire.The results of multiple regression analysis proved the variables of social media and electronic word of mouth, partially or simultaneously have an effect on purchase intention. The influence is a positive effect, if a technology driven online function as participation, conversationality, connectedness, openness, community and commonality, it will encourage consumers topurchase intention at Zalora Indonesia. Furthermore, if the electronic word of mouth gives a positive impression on a product that is offered online through the product involvement, self involvement, Other involvement, and message involvement would increase consumers' intention to buy. From testing the hypothesis that the variables of electronic word of mouth, it turns out the dominant influence on purchase intention.